2013
DOI: 10.3139/105.110196
|View full text |Cite
|
Sign up to set email alerts
|

The Ideal Quenching Medium? – Characterisation of Ionic Liquids for Heat Treatment of Metallic Components

Abstract: Quenching as a part of heat treatment is an important process in the manufacturing chain of metallic components. One of the most common processes is immersion quenching in vaporising liquids. Unfortunately, this process is affected by the Leidenfrost-phenomenon. This effect can generate inhomogeneous quenching and thus asymmetrical residual stresses and avoidable distortion. In this work, ionic liquids have been investigated as new quenching media, which can be used as baths near room temperature. Aluminium cy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…The boiling point of the quenching medium must be avoided because of the unfavorable Leidenfrost phenomenon. [40][41][42][43] Because of our reliable estimation of the boiling point for [EMIm][NTf 2 ], which exceeds twice the commonly acknowledged range of T b for typical ILs, the search for high temperature applications for common ILs can be extended significantly.…”
Section: Resultsmentioning
confidence: 99%
“…The boiling point of the quenching medium must be avoided because of the unfavorable Leidenfrost phenomenon. [40][41][42][43] Because of our reliable estimation of the boiling point for [EMIm][NTf 2 ], which exceeds twice the commonly acknowledged range of T b for typical ILs, the search for high temperature applications for common ILs can be extended significantly.…”
Section: Resultsmentioning
confidence: 99%
“…11 Thus, its application in a number of applications is investigated accompanied by fundamental research as well to understand its behaviour. 14 The heat treatment processes oen contain a quenching step yielding in a short term thermal stress for the liquid used. 12 Hydrogen production in aromatic and aliphatic ionic liquids was researched by Dhiman and LaVerne.…”
Section: Introductionmentioning
confidence: 99%
“…It should be noted that 3.5% w/w of water was added to the IL in order to increase the cooling rate. 9 The rapid drop of the temperature within the rst seconds indicates a very good heat transfer. For water there is only a slight decrease of the temperature for almost ten seconds, which is due to lm boiling.…”
Section: Aluminum Quenchingmentioning
confidence: 99%
“…However, we have recently demonstrated that ILs come quite close to these specications. 9 Due to low melting points, in many cases below room temperature, and their extremely low vapor pressure, as well as high stability towards short-term temperature stress, ILs can be considered as promising candidates for quenching media. In contrast to immersion baths containing salt or metal melts, ionic liquids can be employed at room temperature.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation